Efusi Pleura Ganas e.c. Adenocarcinoma Paru - Indra Buana; Arvinnia Tanida Harefa (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Pleural effusion is a condition in which fluid accumulates in the pleural space. Many diseases may underlie the occurrence of pleural effusion including tuberculosis, malignancy, pneumonia, thoracic empyema, congestive heart failure, and liver cirrhosis (1, 2). In western countries, pleural effusion is mainly caused by congestive heart disease, liver cirrhosis, malignancy, and bacterial pneumonia. While in developing countries like Indonesia it is common to be caused by tuberculosis infection.